KAPASITAS PENINGKATAN POPULASI TERNAK RUMINANSIA BERDASARKAN POTENSI LIMBAH TANAMAN PANGAN SEBAGAI PAKAN TERNAK DI KABUPATEN LAMPUNG SELATAN - Dina Ayu Zahara; Liman ,; Muhtarudin . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The purpose of this research was to observe the potential of crop residues as the alternative forage feed to development of ruminant livestock in South Lampung Regency.This research was carried out in South Lampung Regency on December 2015 until April 2016.This research used survey method with Purposive Sampling. Edible Porpotion or portion that can be consumed based on the calculation of this research, the total production of crop residues based on dry maatter of the three materials was 611.257 tons per year. The result of this research showed that the carrying capacity in 17 subdistricts located in South Lampung regency based on Animal Unit (AU) were 268.095,00 AU. The Concentration Index Livestock based on the calculation in South Lampung Regency has a range valeu from 0,15 until 2,49 by the average valeu was 1,00. Based on the calculation of ruminant livstock population increase capacityobtained the highest grade in Palas Subdistrict of 25.351 AU, but there was four of subdistricts that has value minus is Jati Agung, Merbau Mataram, Sidomulyo and Rajabasa Subdistrict so it was not potential to increase number of ruminant livestock if only rely on carring capacity from residues crops. Keywords : Residues Crops Production, Carring Capacity, IKT, KPPTR